2021
DOI: 10.1177/26323524211032983
|View full text |Cite
|
Sign up to set email alerts
|

Dissemination, use, and impact of a community-based, conversational advance care planning intervention: ripple effects of the Swedish DöBra cards

Abstract: Introduction & Aim: Despite increasing interest in community-based advance care planning interventions, few studies investigate the societal impact of such initiatives. The DöBra cards, a Swedish adaptation of the GoWish cards, were first used for advance care planning conversations in a participatory action research project and later, due to popular demand, made available for purchase by the general public. We explore how the DöBra cards were disseminated and used publicly, to understand their impact in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…In alignment with this, other ACP interventions that have emphasized conversation, for example, by using cards or games, have been reported. 8,20 While it is not surprising that most of the organizations that adopted our model were Hospice Societies (19/22), 7,21 it is important to note that Hospice Societies are not the only type of community organization suitable for implementing this model. For instance, church-based models have been described as effective in community-led ACP education initiatives.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In alignment with this, other ACP interventions that have emphasized conversation, for example, by using cards or games, have been reported. 8,20 While it is not surprising that most of the organizations that adopted our model were Hospice Societies (19/22), 7,21 it is important to note that Hospice Societies are not the only type of community organization suitable for implementing this model. For instance, church-based models have been described as effective in community-led ACP education initiatives.…”
Section: Discussionmentioning
confidence: 99%
“…That has led to increasing recognition of the role of non-clinicians, such as community members, in ACP facilitation. [7][8][9][10] These community-led ACP initiatives hold great potential in increasing public awareness and engagement, leading to a much-needed culture shift that makes ACP engagement the norm for everyone. 10 In the Canadian province, British Columbia (BC), two community-based organizations, Comox Valley Hospice Society (CVHS) and the Community Engagement Advisory Network (CEAN) within Vancouver Coastal Health Authority, have emerged as leaders in community-led ACP education.…”
Section: Introductionmentioning
confidence: 99%
“…Community-based ACP interventions (e.g. DöBra cards in Sweden [ 30 ]) may also benefit families who are uncomfortable talking about EOL issues. Evidence has shown that it was easier for physicians to initiate ACP discussions with informed patients and relatives [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Games have been shown to lower reluctance and resistance when discussing potentially uncomfortable topics such as death, dying, and end-of-life care [6] and can thus be helpful in supporting individuals in thinking and talking about ACP and end-of-life values and preferences. One card game that has shown positive results in stimulating discussion in various studies is the American Go Wish card game (developed the mid 90s by Coda Alliance, a U.S.-based non-profit organization) [7][8][9][10][11][12][13][14][15][16][17][18]. The card game consists of preformulated statements to initiate and support ACP discussions by identifying values and preferences about end-of-life issues and death and dying.…”
Section: Open Accessmentioning
confidence: 99%
“…The Go Wish cards have been tested in the United States, e.g., with patients on inpatient services [13] and with patients with mild cognitive impairment [11]. Moreover, the Go Wish game has been translated and adapted from its source context to use in other groups, e.g., with parents of children with a life-threatening illness [14], as a teaching tool with medical students [10] and in other cultures, e.g., in Sweden, France, China [7,8,[15][16][17][19][20][21][22][23][24].…”
Section: Open Accessmentioning
confidence: 99%